1999
DOI: 10.1002/(sici)1098-2795(199911)54:3<244::aid-mrd5>3.3.co;2-x
|View full text |Cite
|
Sign up to set email alerts
|

Chimeric pigs following blastocyst injection of transgenic porcine primordial germ cells

Abstract: Porcine primordial germ cell (PGC) derived cell lines of WAPhGH-transgenic pigs have been established that were able to contribute to chimeras. PGCs were isolated from day 25 to 28 genital ridges of more than 30 individual transgenic fetuses in order to have an easy to follow marker gene. To support undifferentiated growth, cell lines were derived and stable maintained on STO no. 8 feeder cells, a murine embryonic fibroblast cell line expressing recombinant, membrane-bound porcine stem cell factor (SCF). Fifte… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
18
1
1

Year Published

2002
2002
2019
2019

Publication Types

Select...
6
1

Relationship

1
6

Authors

Journals

citations
Cited by 17 publications
(21 citation statements)
references
References 0 publications
1
18
1
1
Order By: Relevance
“…Chimeric piglets derived from pig EG cells have been reported by several groups . In this study, we also confirmed the ability of EG cells to form chimeras.…”
Section: Discussionsupporting
confidence: 90%
See 3 more Smart Citations
“…Chimeric piglets derived from pig EG cells have been reported by several groups . In this study, we also confirmed the ability of EG cells to form chimeras.…”
Section: Discussionsupporting
confidence: 90%
“…We identified that two piglets of eight were chimeras, as indicated by skin pigmentation and DNA analysis. Our results showed a higher contribution of the cultured EG cells in the dead chimera than some reports , that is, the dead chimera showed detectable chimerism in up to five of 13 tissues analyzed: EG cells contributed to tissues derived from all three germ layers, including skin, brain, pancreas, thyroid gland, and blood. More work should be performed about the alive chimeric pig to determine the pluripotency of the EG cells.…”
Section: Discussioncontrasting
confidence: 47%
See 2 more Smart Citations
“…1999; Vackova et al. 2007) nor primordial germ cells (Mueller et al. 1999) have been isolated in domestic species (Cibelli et al.…”
Section: Generation Of Transgenic Animals Expressing Oct4 Promoter Comentioning
confidence: 99%